Assessment of Nutritional Status in Children with Cancer and Effectiveness of Oral Nutritional Supplements - Kokab Parveen, Tahira Abid, Tayyaba Iftikhar, Muhammad Qasim Khan, Nehal Gul, Abdul Khaliq, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Malnutrition can significantly affect cancer outcomes, but it may be managed through oral nutritional supplements. Objective: The aim of this study was to assess the nutritional status of children with cancer and the effectiveness of oral nutritional supplements. Materials and Methods: This multicentre study was carried out at MMC, DHQ hospital Kohat, AWKUM, KUST following approval from the ethical board of the institutions. The study duration was six months from March 2023 to September 2023. A total of 50 children with newly diagnosed cancer who could ingest an oral diet and were receiving cancer therapy were included. At diagnosis, children with malnutrition received nutrition intervention from a registered dietitian. They were randomly assigned to receive either protein- and energy-dense isocaloric supplements or hypercaloric supplements such as Resource Junior. The nutritionist monitored the supplements intake. Participants were monitored up for 6 months, with nutritional assessments performed at the third and sixth month. Participants' serum samples were tested for plasma albumin, protein, and prealbumin at the time of diagnosis, and again at the third and sixth month. Data were analyzed using SPSS version 18 and presented as mean ± standard deviation. Results: A total of 50 children recently diagnosed with cancer were enrolled out of which were 30 males (60%) and 20 females (40%). Malnutrition was diagnosed in 48% of individuals who met at least one of the following criteria: BMI <5th percentile, weight-for-height <90%, triceps skinfold thickness or mid-upper-arm circumference <5th percentile, or >5% weight loss prior to illness onset. Malnutrition was observed in 34% of patients with intra-abdominal tumors. In the second three months following diagnosis, the number of malnourished patients reduced from 50% to 22%, with statistical significance (P=.006). The number of patients with WFH <90% and BMI <5th percentile decreased significantly (P = .003 and P = .04, respectively).There was a significant variation in mean blood prealbumin levels between the first, third, and sixth months (P=005). Serum albumin levels increased significantly from the first to 3rd and 6th months (P <.001). Conclusion: The current study concluded that malnutrition is a major complication among children with cancer, and oral nutritional supplements are beneficial in preventing weight loss in malnourished individuals. Keywords: Assessment; Nutritional status; Children; Cancer.